Ultrasonic-assisted extraction of phenolic and antioxidative compounds from lizard tail (Houttuynia cordata Thunb.) - Trakul Prommajak (2018)
Lizard tail (Houttuynia cordata Thunb.) is an Asian herb which has many biological activities, including antioxidative property from polyphenolic compounds. Response surface methodology and Box-Behnken design were employed to study the effect of extraction temperature (30 to 70°C), extraction time (10 to 30 min), ethanol concentration (30 to 70%), and solvent to sample ratio (2 to 6 ml/g) on ultrasonic-assisted extraction of phenolic compounds from lizard tail and antioxidant capacity of the herb extract. Extraction temperature was the most relevant factor on the responses. Optimal condition was the extraction temperature of 70°C for 30 min, using 60% ethanol concentration at the solvent to sample ratio of 5 ml/g. Model adequacies were confirmed by extraction at the optimal condition and normality of standardized residuals.